A comprehensive system for the environmental impact assessment of emerging activities of the "new rural scenario" - Rodrigues, Geraldo Stachetti; Campanhola, Clayton (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this paper was to present the Environmental Impact Assessment System of New Rural Activities (APOIA-NovoRural), which consists of a set of electronic spreadsheets (MS-Excel platform) that integrate 62 indicators of environmental performance of an economic activity at the farmstead level. Five assessment dimensions were considered: landscape ecology, environmental quality (atmosphere, water and soil), sociocultural values, economic values and management. Each indicator was constructed into a weighing matrix in which field- and laboratory-obtained data with the appropriate measurement units were automatically transformed into impact indices. The impact index for each indicator was translated into a utility value by multi-coefficient functions specifically derived for each indicator. The utility values for all indicators were aggregated to compose the Environmental Impact Index for the activity under consideration. The indicator level output offers a diagnostic tool for farmers, pointing out specific attributes of the activity that may be failing to comply with defined benchmarks. The dimension-wise output shows decision makers the major contributions of the activity towards local sustainable development, facilitating the definition of control actions and promotion measures. Finally, the aggregated Environmental Impact Index is a yardstick of environmental performance, serving as a straightforward certification tool for rural activities.
Keywords: sustainability; evaluation techniques; methods; rural environment; certification